Inpatient rehabilitation facilities: The 3-hour rule. Issue 37 (September 2019) - Forrest, George; Reppel, Alycia; Kodsi, Mina; Smith, Joshua
Abstract : Abstract: The aim of this study was to determine whether patients whose treatment is consistent with the 3-hour rule have better outcomes than patients whose treatment is not consistent with the 3-hour rule. This is a retrospective review of the records of 581 patients. The authors compared the outcomes of 397 patients whose therapy was consistent with the 3-hour rule to the outcomes of 184 patients whose therapy was not consistent with the rule for at least one 7-day period during the stay on an inpatient rehabilitation facility. Patients whose care was consistent with the rule did not have more improvement in function or shorter length of stay than patients whose care was not consistent with the 3-hour rule. There is not good evidence to support the 3-hour rule as a determinant of the care that a patient at an IRF needs to achieve a good outcome.